Improving product reliability and software quality : strategies, tools, process and implementation - Levin, Mark, 1959-; Kalal, Ted T.; Rodin, Jonathan, 1957- (John Wiley & Sons, Inc., 2019)
"This book, which is logically broken into five sections, describes the reliability process in detail and provides useful tools, forms and spreadsheets for implementing the process. The first section discusses why product reliability will be a requirement for survival in the 21st century. Over the past few decades, most manufacturers have mastered the skills needed to produce quality products; however, the same cannot be said about product reliability. This section focuses on the necessity for companies to have effective reliability programs in order to compete in the 21st century. In the second section of the book, the mystery surrounding reliability is unraveled. The reliability process is presented, reliability concepts are discussed and the "reliability toolbox" is explained. This section closes with a discussion on why companies fail after attempting to implement a reliability program. In the third section of the book three steps in successfully implementing a reliability program are discussed. The three steps are: establishing a reliability lab, hiring the right people and implementing the reliability process. The book addresses how the size of a company can impact on implementation decisions and a decision matrix is presented for small, medium and large companies. In section four, the book presents in detail the reliability process along with the tools and techniques needed for implementation. The material is presented in a way that is easy to understand and the process is readily transferable to any organization. The fifth section adds all new content on DfR guidelines"--